Inclusion Reconceptualized: Pre-Service Teacher Education and Disability Studies in Education - Gilham, Chris; Tompkins, Joanne (Canadian Journal of Education/Revue canadienne de l’éducation, 2016)
In this article, two teacher educators describe and explain how they are reconceptualizing a pre-service teacher education course on inclusion using disability studies in education (DSE) scholarship. The DSE approach better connects the oft-separated field of diversity and inclusion, and builds on the program’s overall focus on equity education. Using a critical reflective self-study approach, these researchers weave together scholarship about inclusive education with their lived classroom experiences in a teacher education program. They conclude that cultivating practical judgement in pre-service teachers is important to inclusive education.